Vallejo the Poet, Vallejo the Journalist: "Two Spirits" in the Same Writer - Gatgens Céspedes, José Alberto (2011)
In this paper, the author analyzes two news chronicles of the great Peruvian poet César Vallejo under the criterion that poet and reporter were never apart without the need of splitting or anti-mater encounters.